Expression Pattern of Myogenic Regulatory Transcription Factor mRNAs in the Embryo and Adult Labeo rohita (Hamilton, 1822) - Sengupta, Archya; Mukherjee, Sandip; Bhattacharya, Shelley; Saha, Samar Kumar; Chattopadhyay, Ansuman (International Journal of Zoology, 2014)
Understanding the regulation of skeletal muscle development is important to meet the increasing demand of Indian major carp Labeo rohita. Myogenic regulatory factors (MRFs) along with myocyte specific enhancer factor 2 (MEF2) play the pivotal role in the determination and differentiation of skeletal muscle. The majority of skeletal muscle genes require both MRFs and MEF2 family members to activate their transcription. In this study, the expression pattern of MyoD, myf-5, myogenin, and MEF2A was observed from 6 h after fertilization to 12 months of age using semiquantitative RT-PCR as well as real-time PCR method. MyoD and myf-5 mRNAs were expressed at high level at the early embryonic stages. Myogenin and MEF2A were expressed after MyoD and myf-5 and remained active up to adult stage. Expression of MyoD was lower than that of Myf-5 after the 5th month. Partial sequencing of MyoD, myf-5, and MEF2A was done to draw phylogeny. In phylogenetic study, Labeo MyoD, MEF2A and myf-5 were found to be closely related to those of common carp. The present investigation suggests that the four transcription factors play pivotal role in the regulation of muscle growth of Labeo rohita in an overlapping and interconnected way.